CURRENCY OF THE MICROFLORA CORRECTION WHEN BEGINNING FEEDING WITH ADDITIONAL FOOD AND ARTIFICIAL MILK FORMULAS - N. V. Toptchiy; A. S. Toporkov; Yu. M. Devyataeva (Вопросы современной педиатрии, 2012)
Children feeding with breast milk have significantly lower risk of gastrointestinal infectious diseases development, than children feeding with artificial milk formulas. At the beginning of feeding with additional food influence of allogenic antigens on child’s organism is increasing, which can lead to disturbances in microbiocoenosis of the gastro-intestinal tract. This causes stool disorders, intestinal colic, dyspepsia, dermatitis, allergic reactions, immunodeficiency with recurrent relapses of infections and development of non-infectious disease and their transition into chronic condition. Forming of the malabsorption syndrome at the background of such conditions leads to growth and mental development retardation of children. Numerous clinical trials proved the beneficial effects of the probiotic Hylak Forte on intestinal microflora in disbiosis.